Essential function of the transcription factor Rax in the early patterning of the mammalian hypothalamus - Orquera, Daniela Paula (2016)
The hypothalamus is a region of the anterior forebrain that controls basic aspects of vertebrate physiology, but the genes involved in its development are still poorly understood. Here, we investigate the function of the homeobox gene Rax/Rx in early hypothalamic development using a conditional targeted inactivation strategy in the mouse. We found that lack of Rax expression prior to embryonic day 8.5 (E8.5) caused a general underdevelopment of the hypothalamic neuroepithelium, while inactivation at later timepoints had little effect. The early absence of Rax impaired neurogenesis and prevented the expression of molecular markers of the dorsomedial hypothalamus, including neuropeptides Proopiomelanocortin and Somatostatin. Interestingly, the expression domains of genes expressed in the ventromedial hypothalamus and infundibulum invaded dorsal hypothalamic territory, showing that Rax is needed for the proper dorsoventral patterning of the developing medial hypothalamus. The phenotypes caused by the early loss of Rax are similar to those of eliminating the expression of the morphogen Sonic hedgehog (Shh) specifically from the hypothalamus. Consistent with this similarity in phenotypes, we observed that Shh and Rax are coexpressed in the rostral forebrain at late head fold stages and that loss of Rax caused a downregulation of Shh expression in the dorsomedial portion of the hypothalamus.